Does Body Mass Index Cause a Clinical Difference in Simultaneous Bilateral and Unilateral Knee Arthroplasty? - Ogur, Hasan Ulas; Cicek, Hakan; Seyfettinoglu, Fırat; Tuhanioglu, Ümit; Aydoğdu, Ali; Kılıcarslan, Kasım (The Journal of Knee Surgery, 2020)
This study aims to investigate clinical and functional factors in patients undergoing unilateral and simultaneous bilateral total knee arthroplasty (TKA) who were classified into subgroups of nonobese, obese, and morbidly obese, and to determine perioperative and postoperative complications. We conducted an evaluation of 489 nonobese, obese, and morbidly obese patients who underwent TKA due to primary knee osteoarthritis between January 2006 and December 2013. The arthroplasties were performed by three different surgeons. Patients who underwent unilateral (group 1) or simultaneous bilateral (group 2) TKAs were divided into subgroups in accordance with BMI levels, that is, (a) nonobese (BMI < 30 kg/m2), (b) obese (BMI = 30–34.9 kg/m2), and (c) morbidly obese (BMI ≥35 kg/m2). Clinical and functional assessments were performed using Knee Society Scores (KSSs), the Western Ontario and McMaster Universities Osteoarthritis index (WOMAC), and range of motion (ROM) values. Perioperative and early postoperative complications were assessed. The mean follow-up period was 46.65 months (minimum: 24 months; maximum: 84 months). There were no significant differences between the patients undergoing unilateral or simultaneous bilateral TKA procedures regarding postoperative ROM, WOMAC indices, and KSSs (p > 0.05), except for morbidly obese patients. Most intraoperative and early postoperative complications occurred in the morbidly obese group, especially in those undergoing simultaneous bilateral TKA procedures (p < 0.001). Unilateral and simultaneous bilateral TKA procedures showed no differences regarding ROM, clinical scores, and perioperative and early postoperative complications in nonobese and obese patients. A moderate increase was detected in complication rates in the unilateral TKA morbidly obese patients (group 1c); however, morbidly obese patients constituted the major risk group in simultaneous bilateral TKA patients (group 2c) regarding clinical scores (lower WOMAC scores and KSSs) and the development of complications.
Keywords: body mass index; unilateral total knee arthroplasty; bilateral total knee arthroplasty